Study on the correlation between adult drinking behavior characteristics and obesity index in China - Xu, X; Zhou, M; Gao, R; Guo, Y; Tian, X; Bian, Z; Tan, Y; Pei, P; Yu, C; Wang, S; Chen, Z; Li, L; et al. (Chinese Journal of Epidemiology, 2019)
Objective: To evaluate the correlation between alcohol consumption and obesity in adults in China. Methods: The information about alcohol consumption were collected at the baseline survey of the China Kadoorie Biobank. The general obesity and central obesity were defined by BMI and waist circumference (WC) respectively. Logistic regression model was employed to examine the relationship of drinking behavior with general obesity and central obesity. Results: A total of 249 873 adults were included. A J-shaped relationship was observed between alcohol consumption and obesity measurement index (BMI and WC) in men. Compared with non-drinkers, the proportion of general obesity and central obesity were lower in light drinkers (men: OR=0.65, 95%CI: 0.59-0.71 and OR=0.93, 95%CI: 0.88-0.98; women: OR=0.77, 95%CI: 0.65-0.91 and OR=0.89, 95%CI: 0.80-0.99). In men, the proportion of general obesity and central obesity was highest in heavy drinkers (OR=1.21, 95%CI: 1.12-1.32; OR=1.33, 95%CI: 1.27-1.40). BMI and WC were higher in those with a drinking frequency of 3-5 d/week, with largest of proportion of central obesity (men: OR=1.23, 95%CI: 1.16-1.31; women: OR=1.13, 95%CI: 0.99-1.28). The risk for central obesity in men who began drinking every week before 20 years old was 1.24 times higher than non-drinkers (95%CI: 1.16-1.33). Those who drank beer had lower proportion of general obesity (men: OR=0.74, 95%CI: 0.67-0.82; women: OR=0.54, 95%CI: 0.43-0.68). Conclusion: The proportion of obesity was lower in light drinkers but higher in heavy drinkers; and the earlier drinking started, the higher the risk for obesity was.